(untitled) (Docentes 2.0 Journal, 2025)
Reading comprehension (LC) is the ability to understand and interpret what is read, with great relevance in teaching basic sciences. The objective of the research was to analyze the bibliographic sources on the current state of LC in teaching basic sciences to children in schools around the world. This research was based on the systemic method, with an interpretive paradigm, a qualitative approach, and a descriptive narrative design of a literary documentary type. Digital recording was used as a technique with the support of the Zotero reference manager and the PRISMA 2020 methodology. The universe focused on articles published until June 2024 in 3 databases: Scopus, Web of Science (WoS), and SciElo, in which 30 articles were obtained as a sample for this review. The results highlighted the role of implementing instructional strategies in improving LC and learning, especially in 4th-grade children from Turkey. It was concluded that LC is a fundamental process for children’s learning of basic sciences. However, due to the heterogeneity of the various methods, future studies need to evaluate individual efficacy through prospective studies or trials.